The role of pathogenic microorganisms in the pathogenesis of scleroderma - Ruoyun LIU; Litian ZHANG; Yue ZHANG; Bin YANG (Pifu-xingbing zhenliaoxue zazhi, 2023)
Systemic sclerosis (SSc) is an autoimmune connective tissue disease characterized by localized or widespread sclerosis of the skin and progressive sclerosis in the internal organs. The pathogenesis of this disease has not been completely elucidated. However, it is considered to be associated with environmental factors, epigenetic mechanisms, and disorders of the immune system. This article reviews the research progress on the role of pathogenic microorganisms in the pathogenesis of scleroderma. It has been shown that scleroderma can be induced by infections with viruses, bacteria, mycoplasma, parasites, and other pathogenic microorganisms. Human herpesvirus and viruses such as B19V and HBV can cause pathological changes such as endothelial dysfunction and fibroblast activation. Alterations in the microbiota inside and outside the body are also associated with SSc. Treatments of pathogenic microorganisms improve SSc associated with infections by pathogenic microorganisms such as C burnetii, Mycoplasma and parasites, providing evidence of new insights in the pathogenesis of SSc, and early diagnosis, intervention and the treatment of this disease.